Culture in early childhood education: Insights into Saudi preschool teaching - Ahlam Abdullah Alghamdi (Intelektual Pustaka Media Utama, 2023)
Culture is constructed by society and in turn constructs the identity of a people. The patterns of behaviors, practices, and values shared by a group of people represent and reflect their ethnic, religious, and gender orientations. Knowledge about people’s cultural backgrounds contributes to our understanding of the role of education in shaping past, present, and future generations. Therefore, this study explores preschool teachers’ cultural views regarding the teaching of young children in a Saudi early childhood education setting. A phenomenological qualitative research approach is used in this study. Data are collected through semistructured focus group interviews with 10 preschool teachers who teach young children in public preschools located in the western region of Saudi Arabia. The thematic analysis of the qualitative data reveals two main themes in the teachers’ narratives: i) Religion-based instruction; and ii) Gender-related issues. The participants in this study reported engaging in a set of practices that showed how their cultural identities, including their nationality, gender, religious beliefs, and history, influenced their roles as educators. Within the rich cultural context of Saudi culture, the teachers reported being strongly committed to their social and spiritual values when teaching young children.